Principles of public international law - Brownlie,Ian (Oxford, 1998)
This is the fifth edition of the leading textbook on Public International Law. The material has been thoroughly revised and updated to take account of developments since 1990, and a new chapter on international environmental protection has been added. The book retains all its original strengths - clear exposition, rigorous analysis, detailed referencing and comprehensive coverage.
Keywords: International Law